Coffee Market Liberalization and Private Sector Performance in Tanzania - Mwakaje, Agnes Godfrey (Indian Journal of Marketing, 2012)
In the traditional neo-classical view, a high market share usually implies market power and exploitation of consumers or producers. However, following high transaction cost of marketing in developing countries, concentrated markets can sometimes be seen as efficient outcomes of competitive behaviour. This paper analyzes the performance of coffee traders in Rungwe District Tanzania following market liberalization in 1994. The focus of the study was on market share, producer price and gross margins across the 11 coffee-buying companies which participated in the 2008/9 marketing season. Using Concentration ratio and Herfindal Index techniques, the results show a high market concentration suggesting that only few companies were controlling a large share of the coffee trade in the district. Nevertheless, there was no strong evidence to suggest that traders were exploiting farmers as companies’ gross margins were modest and producer price increased as compared to the period before the market liberalization. High marketing costs resulting from expensive and time-consuming licensing procedures, poor transport infrastructure and low coffee production levels seem to erode most of the coffee profits in the district.